Pengaruh Kompetensi Pedagogik Guru Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas IX Di SMP Negeri 2 Muara Kabupaten Tapanuli Utara, Tahun Pembelajaran 2023/2024 - Naomi Diasima Simbolon; Risden Anakampun; Wilson Simanjuntak; Pestaria Naibaho; Nurelni Limbong (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to find out how much positive and significant influence Teacher Pedagogical Competence has on the Learning Activeness of Christian Religious Education and Characteristics of Class IX Students at SMP Negeri 2 Muara, North Tapanuli Regency for the 2023/2024 Academic Year. The method used in this research is quantitative with inferential statistical data analysis. The population is all class IX of SMP Negeri 2 Muara, North Tapanuli Regency for the 2023/2024 Academic Year who are Christians, totaling 104 people and a sample of 38 people was determined, namely 35% of the total population. Data was collected using a positive closed questionnaire totaling 36 items, of which 16 questionnaire items were for variable at SMP Negeri 2 Muara, North Tapanuli Regency, Academic Year 2023/2024: 1) Test the analysis requirements: a) positive relationship test, obtained a value of rxy = 0.552 > rtable(=0.05,n=38) = 0.320, thus it is known that positive relationship between variable variable Y. 2) Influence test: a) Test the regression equation, obtained the regression equation Y ̂="26","01"+0.75X. b) Regression coefficient of determination test (r2) = 30.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=20, dk denominator=n-2=38-2=36) namely 15.74 > 1.51. Thus Ha is accepted and H0 is rejected.